Type-C port locking device - LIU XIAOJUN; TANG FENG; LIU XIAN; FANG SICONG (2025)
The utility model discloses a locking device for a type-C port. According to the type-C port closing device, a type-C port comprises a pin connector, and the pin connector comprises a limiting protrusion; a lock body; the plug is mounted on the lock body, and the plug has a stretching-in state in which the plug can stretch into the type-C port and a retreating state in which the plug retreats from the type-C port; the locking piece is movably arranged in the lock body, the locking piece has an unlocking state and a locking state, in the locking state, the locking piece is matched with the limiting protrusion in a limiting mode so as to prevent the plug from retreating from the type-C port, in the unlocking state, the locking piece can release the limiting protrusion, and the plug can retreat from the type-C port; the locking assembly is mounted on the lock body, and the locking assembly is used for driving the locking piece to move so as to switch the state of the locking piece. According to the type-C port l